2022
DOI: 10.1002/fsh.10727
|View full text |Cite
|
Sign up to set email alerts
|

Science vs. Sensationalism: Lessons for Science Communication in Fisheries from Netflix’s Seaspiracy

Abstract: The Netflix documentary Seaspiracy portrays serious issues driven by illegal and exploitative fishing, including stock collapse, habitat destruction, biodiversity loss, perverse subsidies, high seas crime, human labor abuses, and modern slavery. Certainly, an alarming number of fisheries remain overfished and exhibit these issues, particularly in places where industrialized fleets exploit waters that lack the capacity for management and enforcement (Worm et al. 2009). However, the film's omission of any succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The thematic and narrative parallels of Cowspiracy and Seaspiracy encourage a conception of the two films as forming a hermeneutic unity. The combined analysis of the two documentaries thus draws on the theoretical sources referred to in the previous section while also considering scholarly output on Cowspiracy (Lockwood, 2016;Weik von Mossner, 2021) and Seaspiracy (Lamb, 2021;Hearne, 2021;Pauly, 2021;Belhabib, 2021;Rooney, 2022;Harris, 2022;Yeo & Silberg, 2022). A qualitative approach is adopted to assess the films' discursive strategies, using the tools offered by film analysis.…”
Section: Emotion In Documentaries As a Force For Changementioning
confidence: 99%
See 1 more Smart Citation
“…The thematic and narrative parallels of Cowspiracy and Seaspiracy encourage a conception of the two films as forming a hermeneutic unity. The combined analysis of the two documentaries thus draws on the theoretical sources referred to in the previous section while also considering scholarly output on Cowspiracy (Lockwood, 2016;Weik von Mossner, 2021) and Seaspiracy (Lamb, 2021;Hearne, 2021;Pauly, 2021;Belhabib, 2021;Rooney, 2022;Harris, 2022;Yeo & Silberg, 2022). A qualitative approach is adopted to assess the films' discursive strategies, using the tools offered by film analysis.…”
Section: Emotion In Documentaries As a Force For Changementioning
confidence: 99%
“…Both films have been the subject of criticism for their subjective approach. In this sense, Tabrizi's film is the one that has generated the strongest backlash among those who argue that the hero's journey is a conveniently fictionalized reconstruction (Hearne, 2021) or that the film seems more concerned with a kind of verisimilitude ("truthiness") than with truth (Yeo & Silberg, 2021, p. 781) and abandons the scientific objectivity that one would expect from a documentary (Harris, 2022). Similarly, some have suggested that the film presents biased data in a sensationalist manner and does not consider other perspectives on the issue (Yeo & Silberg, 2021, p. 782;Pauly, 2021).…”
Section: The Use Of Fiction (Ii): First-person Narration and Identifi...mentioning
confidence: 99%
“…Whilst there are only a few documented cases where scientists and scientific consultants employed by the fishing industry or other stakeholders have 'bent' scientific evidence in favor of the industry or conservation purposes, or have contested the scientific process (Starr et al, 1998;Loring, 2017;Moore et al, 2018;Kraan et al, 2020;O'Brien, 2022), such cases have contributed to the perception that stakeholderemployed scientists should be regarded with suspicion. However, there are also cases where scientists from marine institutes or academia, using their institutional credentials in the name of the scientific advice committee they are a member of, have acted as advocacy scientists in support of stakeholder views (Rice, 2011;Steins et al, 2020b;Mossler, 2021;Harris, 2022;Hutchings, 2022) or have selectively used information in science communications as a commodity seeking to polarize views to highlight debate and garner readership, instead of promoting understanding (for example, Pauly et al, 2013;Harris, 2022). Finally, there are also (mostly un-documented) examples from Europe and Canada where government, not industry or conservation stakeholders, has put pressure on scientists to advocate specific positions (e.g., Hutchings, 2022).…”
Section: Issue 3: Integrity Of Sciencementioning
confidence: 99%
“…Whilst there are only a few documented cases where scientists and scientific consultants employed by the fishing industry or other stakeholders have 'bent' scientific evidence in favor of the industry or conservation purposes, or have contested the scientific process (Starr et al, 1998;Loring, 2017;Moore et al, 2018;Le Manach et al, 2019;Kraan et al, 2020;O'Brien, 2022), such cases have contributed to the perception that stakeholderemployed scientists should be regarded with suspicion. However, there are also cases where scientists from marine institutes or academia, using their institutional credentials in the name of the scientific advice committee they are a member of, have acted as advocacy scientists in support of stakeholder views (Rice, 2011;Steins et al, 2020b;Mossler, 2021;Harris, 2022;Hutchings, 2022) or have selectively used information in science communications as a commodity seeking to polarize views to highlight debate and garner readership, instead of promoting understanding (for example, Pauly et al, 2013;Harris, 2022). Finally, there are also (mostly un-documented) examples from Europe and Canada where government, not industry or conservation stakeholders, has put pressure on scientists to advocate specific positions (e.g., Hutchings, 2022).…”
Section: Issue 3: Integrity Of Sciencementioning
confidence: 99%